2010
DOI: 10.1088/1468-6996/11/4/044402
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bi and Fe co-doped PZT capacitors for FeRAM

Abstract: Ferroelectric random access memory (FeRAM) has been in mass production for over 15 years. Higher polarization ferroelectric materials are needed for future devices which can operate above about 100• C. With this goal in mind, co-doping of thin Pb(Zr 40 , Ti 60 )O 3 (PZT) films with 1 at.% Bi and 1 at.% Fe was examined in order to enhance the ferroelectric properties as well as characterize the doped material. The XRD patterns of PZT-5% BiFeO 3 (BF) and PZT 140-nm thick films showed (111) orientation on (111) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…Many investigations have been conducted to obtain piezoelectric ceramics with a high d 33 value and small K 33 T [17][18][19]. From considerations of ionic radii, it is probable that bismuth (Bi) and yttria (Y) ions occupy the Pb site, and that charge compensation will take place by the creation of Pb vacancies in the lattice, which facilitate the movement of the domain wall so as to improve the piezoelectric and dielectric properties [20][21][22][23][24][25]. It was reported that the substitution of Bi in PZT increased sinterability, retarded grain growth, and decreased grain size [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations have been conducted to obtain piezoelectric ceramics with a high d 33 value and small K 33 T [17][18][19]. From considerations of ionic radii, it is probable that bismuth (Bi) and yttria (Y) ions occupy the Pb site, and that charge compensation will take place by the creation of Pb vacancies in the lattice, which facilitate the movement of the domain wall so as to improve the piezoelectric and dielectric properties [20][21][22][23][24][25]. It was reported that the substitution of Bi in PZT increased sinterability, retarded grain growth, and decreased grain size [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…From considerations of ionic radii, it is probable that bismuth (Bi) and yttria (Y) ions occupy the Pb site, and that charge compensation will take place by the creation of Pb vacancies in the lattice, which facilitate the movement of the domain wall so as to improve the piezoelectric and dielectric properties [20][21][22][23][24][25]. It was reported that the substitution of Bi in PZT increased sinterability, retarded grain growth, and decreased grain size [22][23][24]. In addition, it was also reported that a uniform grain size distribution with decreasing grain size yielded a large P r and a small leakage current in Y-doped PZT materials [20,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…A PUND (positive-up negative-down) polarization test is a powerful tool to probe the ferroelectric behavior of a ferroelectric material; the transient current estimated with PUND is related to the leakage current of a ferroelectric material [47][48][49][50][51]. 1C showed a small transient current, less than 0.02 mA, which is as small as in the previous work of BFO single layer measured at low temperature (93 K) [48].…”
Section: Resultsmentioning
confidence: 75%
“…As the Fe 2 O 3 doped into PZT ceramics can effectively create defect dipoles and increase the net polarization [67], Yoon et al [68] [70]. Later, they selected the alkaline-earth metal ion of Sr 2+ which has the same valence as Pb 2+ to optimize the electrical properties of PZN-PZT ceramics.…”
Section: Oxides Doping To Pzt-based Ceramicsmentioning
confidence: 99%